The Conformity Analysis of English Practicum Courses, English for Midwifery in Midwifery Study Program Faculty of Health Sciences, Alma Ata University, Even Semester, Academic Year 2019/2020 - Susilowati, Ika Tri; Kusuma, Chahya (Universitas Alma Ata, 2021)
It’s different from English course, an English practicum course is English for Specific Purpose. In the midwifery study program, an English practicum course is entitled English for Midwifery. This course specifically discusses skills of prospective midwives in handling patients.This research is a descriptive study with qualitative research method. Data were collected using questionnaire techniques and interviews. The number of respondents in semester II are 12 respondents and semester IV are 22 respondents. Data analysis used the triangulation method by comparing the questionnaire results, interview data and student achievements in the English for Midwifery course.The results of this study indicate that students who have practiced in the practice field will more easily absorb the material in the English practicum course entitled English for Midwifery. Practical experience in the field provides sufficient background knowledge for students to be more involved in the practical.Keywords: English for midwifery, practice field, background knowledge